2005
DOI: 10.1002/ijc.21528
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B alleles, high-risk HPV infection and risk for cervical neoplasia in southern Chinese women

Abstract: A population-based study was conducted on 256 southern Chinese with cervical intraepithelial neoplasia grade III (CIN III) or invasive cervical cancer (ICC) and on 258 controls to examine the associations between HLA-B alleles, infection with high-risk human papillomaviruses (HPVs) and the development of cervical neoplasia. HLA-B15 was found to be protective for CIN III/ICC overall (p corrected 5 0.003), and for HPV52-positive CIN III/ICC (p corrected 5 0.003). A marginal protective effect of B15 was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…A high prevalence of HPV52 and HPV58 among cancer cases was reported previously [Chan et al, 2006a, in press], and similar observations have been reported from other Chinese populations including Shenzhen city and Taiwan [Lai et al, 1999;Lin et al, 2006;Smith et al, 2007]. Previously, we have shown that an HPV58 variant (E6/E7-HK-2) commonly found in Hong Kong was associated with a higher oncogenic risk [Chan et al, 2002]; and certain HLA alleles conferred a cancer risk in an HPV52/58 type-dependent manner [Chan et al, 2006b[Chan et al, , 2007a. Accordingly, if the widespread administration of HPV16/18-based prophylactic vaccines results in the replacement of cervical cancercausing HPV types, it might be shown more readily in these Chinese populations.…”
Section: Discussionsupporting
confidence: 77%
“…A high prevalence of HPV52 and HPV58 among cancer cases was reported previously [Chan et al, 2006a, in press], and similar observations have been reported from other Chinese populations including Shenzhen city and Taiwan [Lai et al, 1999;Lin et al, 2006;Smith et al, 2007]. Previously, we have shown that an HPV58 variant (E6/E7-HK-2) commonly found in Hong Kong was associated with a higher oncogenic risk [Chan et al, 2002]; and certain HLA alleles conferred a cancer risk in an HPV52/58 type-dependent manner [Chan et al, 2006b[Chan et al, , 2007a. Accordingly, if the widespread administration of HPV16/18-based prophylactic vaccines results in the replacement of cervical cancercausing HPV types, it might be shown more readily in these Chinese populations.…”
Section: Discussionsupporting
confidence: 77%
“…This phenomenon indicates that genes belonging to HLA-B7 supertype possibly have the same or similar peptide epitope, unable to present HPV derived-antigen to T cell, leading to high cervical cancer risk. Our initial research on cervical cancer risk focused on HLA-A alleles to find out that HLA-A*0206 had a protective function against cervical cancer creation [29] , which proved that HLA-A*0206 can provide HPV16E7 [11][12][13][14][15][16][17][18][19][20] and the peptide epitope of E7 86-93 to provoke CTL killing function against the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research proves that some HLA alleles have certain correlation to enhancing or reducing cervical cancer risk in different races [7] . Research on the correlation between HLA and cervical cancer is mainly focused on Class II genes [8,9] reports on genetic susceptibility of HLA-I gene are very scarce [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…3). HLA-B*15 and B*1501 have both been strongly associated with a reduced risk of precancerous cervical lesions and cervical squamous cell carcinoma (OR range 0.48–0.6) [40, 42, 46]. HLA-B*15 has also decreased the risk for adenocarcinoma (OR 0.73) [40].…”
Section: Discussionmentioning
confidence: 99%